Equivalent of stimuli’s model and the analysis of anxiety disorder: the effects of experimental history and stimulus characteristics in anxious and non-anxious subjects - Neves, Sônia Maria M.; Vandenberghe, Luc; Oliveira, Lúcia H. R.; Silva, André V.; Oliveira, Kellen C. F. de; Oliveira, Juliana Di S.; Santos, Divina P. dos; Villane, Maria Cristiane S. (Brazilian Journal of Behavioral and Cognitive Therapy, 1999)
Equivalent of stimuli’s model for the analysis of anxiety disorder: the effects of experimental history and stimulus characteristics in anxious and non-anxious subjects. Eight subjects, four anxious and four non-anxious (the free choice group) were exposed to a conditional relation task, with threatening and non-threatening stimuli. The subjects could form homogeneous relations (only threatening stimuli or only non-threatening ones) and mixed relations (threatening and no threatening stimuli). Eight other subjects, four anxious and four non-anxious (the forced choice group) could only form mixed relations. After a training of mixed relations, the non-anxious in the free choice group formed as many mixed classes as homogeneous ones while the anxious, only formed homogeneous relations. In the forced choice group neither neither a nxious nor non-anxious subjects showed any preference to form either one of these types of classes. The data suggest that the difficulty which anxious subjects have in forming mixed relations is due to pre-existing threatening and non-threatening stimulus-classes. Furthermore, a preceding context of forced mixed choices can interfere in the patterns of emergent relations.